The influence of smoking on the periodontal biome. A review. - Lazăr Luminița; Dakó Timea; Cozma Andreea; Lazăr Ana-Petra ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2022)
Periodontal disease is believed to be an opportunistic infection due to the interaction of bacterial plaque and the patient's response that may be influenced by environmental, genetic, and other risk factors. In addition to the fact that smoking is considered a risk factor in many systemic diseases, it has also been associated with the initiation of periodontal disease. Smoking is one of the modifiable risk factors and has a significant influence on the development, progress, and results of the treatment of periodontal disease. The current state in the field of study suggests that smoking aids the colonization of periodontal microorganisms, accelerating the onset of periodontal disease. Biological modifications in pathogens, such as Porphyromonas gingivalis, along with poor immune response, influence the variations of subgingival flora in smoking patients. Only with an individual approach can the risk factors of each patient be identified and satisfactory results obtained. The aim of this paper is to present a comprehensive review of the influence of smoking on periodontal microbiome and the importance of adopting the appropriate treatment method according to the influence of this risk factor on healing.